Vzgliad . Vzgliad . Viewpoint . Взгляд - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Report on the travel of the Great Duchess Maria Vladimirovna in Arkhangelsk Oblast and Murmansk Oblast; interview with Egor IAkovlev, chief editor of "Obshchaia Gazeta" ("Public Gazette"); report on the situation in Chechnya; interviews with a film director IUrii Mamin and artist Sergei Bugaev; segment of homeless children in St. Petersburg. Featured in the program: Makarevich, Andrei Vadimovich (Music Band); Bugaev, Sergei Anatol'evich (Painter) Contributors: Liubimov, Aleksandr Mikhailovich (Anchor); Molchanov, Vladimir Kirillovich (Anchor) Репортаж о поездке великой княгини Марии Владимировны по Архангельской и Мурманской областях; беседа с Егором Яковлевым, главным редактором "Общей Газеты"; репортаж о ситуации в Чечне; беседы с кинорежиссером Юрием Маминым и художником Сергеем Бугаевым; сюжет о петербургских беспризорниках. В программе участвуют: Макаревич, Андрей Вадимович (Музыкальная группа); Бугаев, Сергей Анатольевич (Художник) Создатели: Любимов, Александр Михайлович (Ведущий/Ведущая); Молчанов, Владимир Кириллович (Ведущий/Ведущая)